Microplastics effects in Scrobicularia plana. Issue 1 (15th September 2017) - Ribeiro, Francisca; Garcia, Ana R.; Pereira, Beatriz P.; Fonseca, Maria; Mestre, Nélia C.; Fonseca, Tainá G.; Ilharco, Laura M.; Bebianno, Maria João
Abstract: One of the most common plastics in the marine environment is polystyrene (PS) that can be broken down to micro sized particles. Marine organisms are vulnerable to the exposure to microplastics. This study assesses the effects of PS microplastics in tissues of the clam Scrobicularia plana . Clams were exposed to 1 mg L − 1 (20 μm) for 14 days, followed by 7 days of depuration. A qualitative analysis by infrared spectroscopy in diffuse reflectance mode period detected the presence of microplastics in clam tissues upon exposure, which were not eliminated after depuration. The effects of microplastics were assessed by a battery of biomarkers and results revealed that microplastics induce effects on antioxidant capacity, DNA damage, neurotoxicity and oxidative damage. S. plana is a significant target to assess the environmental risk of PS microplastics. Graphical abstract: Highlights: PS microplastics are uptaken by clam gills and digestive gland where they were accumulated. In the digestive gland they were probably eliminated. Tissue-specific sensibility is involved in clam's responses to oxidative stress. Gills had a more effective response to oxidative stress than digestive gland. PS microplastics genotoxicity and neurotoxicity is time dependent, having an increase in genotoxicity and in neurotoxicity.